A rare case of syndromic severe congenital neutropenia: JAGN1 mutation - Çipe, Funda Erol; Aydoğmuş, Çiğdem; Baskın, Kübra; Keskindemirci, Gonca; Garncarz, Wojciech; Boztuğ, Kaan (The Turkish Journal of Pediatrics, 2020)
Background. Neutrophils are essential innate cells to fight bacterial and fungal pathogens. Jagunal homolog 1 (JAGN1) mutations were recently defined as rare genetic defects causing severe congenital neutropenia. JAGN1 participates in the secretory pathway and is required for granulocyte colony-stimulating factor receptormediated signalling. This gene is required for normal ultrastructure and granulation of endoplasmic reticulum of myeloid progenitor cells. Its defect is related to increased predisposition to apoptosis. In the literature, a few cases have been reported with congenital anomalies such as cardiac and renal anomalies. Case. Here we report a patient in which JAGN1 deficiency was found after several years. Apart from syndromic facial appearance we were unable to detect any other systemic malformations. Conclusion. The causes of multisystemic features of mutations in JAGN1 gene remain unknown. JAGN1 mutations must be considered in patients with severe congenital neutropenia especially with facial dismorphism even in the absence of systemic manifestations.
Keywords: JAGN1 mutation; severe congenital neutropenia